The influence of ants on seeding operations in northern Australian mined areas - Majer, Jonathan (1984)
One method of rehabilitating areas mined for manganese at Groote Eylandt, Northern Territory, and bauxite at Gove, Northern Territory, and Weipa, North Queensland, involves broadcast seeding with native plant species following return of the topsoil. Experiments were performed at each of these areas to see if ants removed seeds of Grevillea, Acacia or Eucalyptus spp. in 3 habitats: original forest vegetation, freshly topsoiled areas (except at Groote Eylandt) and areas which had been rehabilitated >3.5 years previously. Seed removal by ants was generally greatest for the fleshy fringed Grevillea pteridifolia seed and least for the non-arillate Eucalyptus spp. seeds. Removal rates of Acacia spp., which also possess arils, generally fell between the other 2 species. Removal rates of seeds in the >3.5-year-old rehabilitated areas were similar to those in the forest, indicating that the previous ant-seed relationship had been restored by this time . Seed removal by ants was low in the freshly topsoiled areas, except where ants foraged from adjacent rehabilitated areas.